KEDUDUKAN LEMBAGA SERTA TINDAK LANJUT MENGENAI PUTUSAN DEWAN KEHORMATAN PENYELENGGARA PEMILU - C. S, Mikhael Wisnumurti; Michael, Tomy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
According to DKPP Regulation No. 1 of 2021, Second Amendment to Election Organizer Ethics Council Regulation No. 3 of 2017, Regulation No. 3 of the Procedure for the Procedure for the General Election Organizer Code of Ethics Article 39(1), DKPP reserves the right to: make final and binding decisions. However, DKPP Decision No. 317-PKE-DKPP/X/2019 decided to impose a permanent dismissal sentence on Evi Novida Ginting Manik, Commissioner of the The President of the Republic of Indonesia promptly issued Presidential Decree No. 34/2020 P for the disrespectful removal of a member of the General Election Committee for the 2017-2022 term. By PTUN Decision No. 82/G/2020/PTUN-JKT, the judge issued his 2020 Presidential Decree No. 34 regarding the disrespectful dismissal of a member of the General Election Commission from 2017 to his 2022 term. /P overturned. The method of this paper uses a form of research called normative legal research. A method of collecting materials by searching library materials, reading and researching various documents such as books, laws, articles, and other primary, secondary, and tertiary legal codes. The investigation conducted in this letter covers Law No. 7 of 2017, decisions of the Administrative Court, decisions of the DKPP and related Presidential Decrees. Institutionally, the DKPP’s position is equivalent to that of the KPU and Bawaslu, both of which are national, permanent and independent electoral authorities. Considering the Supreme Court’s ruling No. 31/puu-xi/2013, which is final and binding, the DKPP’s decision is definitive and binding on the President, KPU, Provincial KPU, Regency/Municipality KPU, and Bawasul. layout. His final and enforceable DKPP ruling is not the same as a judicial final and enforceable judgment, but it is final and enforceable and comparable to a TUN decision. Institutionally, the Honorary Council of Electoral Organizations (DKPP) status in the Indonesian legal system is either a subordinate body of the government or an independent supporting government agency. In practice, the DKPP’s decisions are not final. This is because it implies the finality of judicial decisions in general and MK decisions in particular. It is so named because the Presidential Decree, Provincial KPU, Regency/Municipality KPU, and Bawaslu, Provincial Bawaslu, Regency/Municipality Bawaslu are still required to implement the decisions of the DKPP